Is it possible to rule out level II and level VB dissection in patients with metastatic papillary thyroid cancer? - Matlim Ozel, Tugba; Akbulut, Sezer; Celik, Aykut; Yildiz, Gorkem; Barut, Hamit Yucel; Dogukan, Fatih Mert; Sari, Serkan (Frontiers in Endocrinology, 2025)
BackgroundThe completeness of surgical resection is a key factor influencing outcomes in patients with papillary thyroid carcinoma (PTC) and regional lymph node metastases. However, the optimal extent of therapeutic lateral neck dissection remains a matter of debate This study aimed to assess the diagnostic accuracy of preoperative ultrasonography (US) in detecting lateral lymph node metastasis (LLNM) in patients with PTC and to identify clinical and pathological factors predictive of metastases at levels II and V.MethodsThis retrospective study included consecutive patients with PTC who underwent comprehensive lateral neck dissection at a single tertiary center between June 2020 and July 2024.ResultsIn 63 patients, a total of 78 comprehensive lateral neck dissections were performed. Of the patients, 41 (65%) were male and 22 (35%) were female, with a median age of 37 years (range, 24–49 years). Lymph node metastases were identified in 46 (58.9%), at level II, 561 (78.2%) at level III, 60 (76.9%) at level IV, and 9 (11.5%) at level Vb. Metastasis to level IIb was detected in 5 dissections. Among the 9 patients with level Vb metastases, 7 (77.8%) had involvement of four different cervical levels. The specificity of US in identifying metastatic disease was notably high at both level II (80%) and level Vb (87%). Independent predictors of metastatic involvement at level II and level Vb lymph nodes was associated with extrathyroidal extension [level II: odds ratio (OR) 7.88, p=0.03; level V: OR 6.91, p=0.043] and a largest metastatic lateral lymph node size above 2 cm [level II: OR 18.58, p=0.03; level V: OR 11.32, p=0.03].ConclusionRoutine dissection of level IIa is recommended in N1b PTC due to high metastasis rates. However, level IIb dissection may be omitted in selected cases given its low metastasis rate and potential morbidity, with intraoperative frozen section serving as a useful guide. Similarly, level Vb dissection may be avoided when lateral lymph nodes are <2 cm, multilevel involvement is absent, and ultrasonographic findings are negative.